Diversity of Fisheries in Sarawak, Northwest Borneo: Present Status and Conservation Issues - MUSTAFA KAMAL, ABU HENA; SINDEN, ANN; IDRIS, MOHD HANAFI; AL-ASIF, ABDULLA-; HAMLI, HADI; MUSA, NAJIAH; PIAH, RUMEAIDA MAT; WAHID, MOHD EFFENDY ABD; LAH, ROSLIZAWATI AB; RASDI, NADIAH WAN; ABUALREESH, MUYASSAR H.; BHUIYAN, MD KHURSHID ALAM; et al. (Borneo Journal of Resource Science and Technology, 2022)
Information on fisheries resources in East Malaysia is scarce and poorly known. The current review aims to compile a checklist of fisheries resources in the Northwest Borneo (Sarawak, Malaysia) from available published literature, address the resources’ present status, and suggest future monitoring needs for selected critical species. The study also aims to determine several Sarawak land-use issues that are in flux and responsible for habitat degradation. Five hundred sixty-four species belonging to 123 families and 32 orders were recorded from Sarawak waters. Freshwater fish species comprised 48.0% of the total, followed by a marine (36.6%), marine-euryhaline (12.9%), and brackish water (2.5%) species. Of this, Cyprinidae was the most dominant group accounting for the greatest number of species (82 species), followed by Balitoridae (34 species), Bagridae (21 species) and Penaeidae (21 species). Therefore, available fisheries resources should be managed carefully as 48 species (9.0%) are currently vulnerable to extinction. Furthermore, the presence of 20 alien species in Sarawak water bodies also requires attention from the authorities due to the potential disruption of aquatic ecological balance. Changing land use issues in Sarawak such as forest degradation, agricultural expansion, peatland deforestation and conversion, logging, destruction of mangrove forests, and construction of hydroelectric power dams and flood mitigation channels pose significant challenges to fishery management in Sarawak. Our study documents the priority of fishery monitoring and conservation in Sarawak water bodies to ensure sustainable management of fisheries resources.